Validasi Islamic Scale of Wisdom-Academic Version dengan San Diego Wisdom Scale dan Papi-Kostick - Fani Eka Nurtjahjo; Ahmad Rusdi; Maudista Widi Anggraeni; Immawati Hanifah; Farida Nur Ummi; Hanum Azizah Destyaputri; Aziza Zulfa Hardiana (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
The concept of wisdom as one of the strengths of human character has been widely studied, both in terms of theoretical concepts and measurements. ISM-AV is the development of a theory-based wisdom measurement instrument from Muslim scholars ibn Miskawaih (2011). The existence of this instrument becomes a necessity to know the extent to which a person assesses his balance in using his mind to produce good actions/attitudes, in an academic context. This study was to validate ISW-AV using external criteria, namely SD-WISE, and PAPI-Kostick (only used aspects: leadership role), need to control others, ease in making decisions, and the theoretical type of thinking. The content validity process involving eight qualified panelists has guaranteed that the items used on this scale are most relevant (CVI > .80). The results of the second study involving 125 student respondents, found that the ISW-AV had similar constructs to the standard wisdom scale (SD-WISE) (r = .550, p =?). Furthermore, the results of the third study involving 666 students found that ISW-AV was positively correlated with leadership roles (r = .261), the need to control others (r = .232), and ease in decision making (r = .114), but negatively correlated with the theoretical type (r = -.117). This finding shows that wisdom is not the same as theoretical intelligence, it is closer to social leadership skills. In conclusion, this scale can be used for further research purposes. For the development of this scale, the process of normalizing and compiling a short form will be very useful to complement the features